The meaning of the floral and faunal scenes in the religious life of the Cuicul community through the Roman stelae - ghouas, zahra; Ramili, nedjma serradj (The Algerian Historical Journal, 2026)
The ancient life went through many stages in which man tried to translate his thoughts and life through the arts, such as drawing and engraving on solid materials. Then, he developed techniques to express them by adopting the meanings and semantics approach to leave his mark, so it was like a hidden language incarnated in many physical forms. The floral and faunal scenes occupied most of the masterpieces left by ancient man, through which he expressed his beliefs and transmitted the meaning of it messages, and that appears on the carvings of the roman stelae in the city of Cuicul, considered as a symbol of belief in human life and as a result of interference of previous civilizations, to form a cultural and intellectual intermix that reflects the level of the ancient human culture.